2006
DOI: 10.1103/physrevlett.97.036402
|View full text |Cite
|
Sign up to set email alerts
|

Green’s Function of a Dressed Particle

Abstract: We present a new, highly efficient yet accurate approximation for the Green's functions of dressed particles, using the Holstein polaron as an example. Instead of summing a subclass of diagrams (e.g. the non-crossed ones, in the self-consistent Born approximation (SCBA)), we sum all the diagrams, but with each diagram averaged over its free propagators' momenta. The resulting Green's function satisfies exactly the first six spectral weight sum rules. All higher sum rules are satisfied with great accuracy, beco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
206
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(214 citation statements)
references
References 13 publications
7
206
1
Order By: Relevance
“…(18). Studies have been performed to assess the validity of such approximation scheme, both at zero temperature via numerical Monte Carlo calculations combined with an analytical expansion in powers of 1/λ, [86] and at finite temperature using a generalization of the so-called momentum-average approximation [87] to non-translationally invariant systems. [48] Such studies have shown that, as was originally devised by Holstein, the band-narrowing approximation can only be applied if the vibrational frequencies are much larger that the unrenormalized electron bandwidth (the so called anti-adiabatic limit, J ω 0 ), because only in this case the phonon cloud can instantaneously re-arrange to follow the motion of the carriers as encoded in Eq.…”
Section: Small Polaron Theory and Extensionsmentioning
confidence: 99%
“…(18). Studies have been performed to assess the validity of such approximation scheme, both at zero temperature via numerical Monte Carlo calculations combined with an analytical expansion in powers of 1/λ, [86] and at finite temperature using a generalization of the so-called momentum-average approximation [87] to non-translationally invariant systems. [48] Such studies have shown that, as was originally devised by Holstein, the band-narrowing approximation can only be applied if the vibrational frequencies are much larger that the unrenormalized electron bandwidth (the so called anti-adiabatic limit, J ω 0 ), because only in this case the phonon cloud can instantaneously re-arrange to follow the motion of the carriers as encoded in Eq.…”
Section: Small Polaron Theory and Extensionsmentioning
confidence: 99%
“…For example, within the new diagrammatic Monte Carlo method [8][9][10], the important problems of high-temperature superconductivity [11] have been solved, and the excited states of structure and structureless Fröhlich polaron [1,2] have been studied exactly and consistently. Recently in [12][13][14][15], a new powerful approach for the investigation of different quasi-particles interacting with phonons in homogeneous and inhomogeneous systems has been developed. It is based on the non-perturbative method of momentum average approximation.…”
Section: Introductionmentioning
confidence: 99%
“…30−35 Analytic approximations have also progressed over the years. 36,37,38,39 For some materials, a more appropriate model is provided by the breathing-mode Hamiltonian. For example, consider a half-filled 2D copper-oxygen plane of a parent cuprate compound.…”
Section: Introductionmentioning
confidence: 99%